Pemetaan Karbon Organik Tanah pada Beberapa Tutupan Lahan dan Kelas Lereng di Kecamatan Simbang Kabupaten Maros: Soil Organic Carbon Mapping in Several Land Cover and Slope Classes in Simbang District, Maros Regency - Nuril Afni, Fify; Baja, Sumbangan; Jayadi, Muh. (Jurnal Ecosolum, 2025)
It is estimated that hundreds of millions of tonnes of carbon stored in soil have been lost due to human activities, primarily through soil cultivation practices and land cover changes. The organic C content in the soil varies, depending on the climate, soil type, mineralogy, land cover and management. The existence of the C-organic distribution map can be a reference in dealing with existing problems, especially in the agricultural sector regarding soil fertility in the region. This study aims to determine the level of soil organic carbon in several types of land cover and slope classes to map the spatial distribution of soil organic carbon in several land covers and slope classes in Simbang District, Maros Regency. Soil sampling was carried out using a drill at a depth of 0-15 cm, for each point a sample was taken. Soil analysis includes c-organic, soil texture, soil color, and bulk density. Making maps of the distribution of soil organic carbon using ArcGIS spatial analysis with interpolation techniques. The highest soil C-organic content was obtained in secondary forest land cover with slopes of 0-8% (flat) with a bulk density value of 1.05 g/cm3 and a color of 7.5YR 3/3 dark brown. The lowest C-organic content was obtained in scrub land cover with a slope of 8-15%, namely 1.21% with a bulk density value of 1.50 g/cm3 and a color of 5YR 4/4 reddish brown. In addition, the soil texture results also showed that the highest clay fraction content was found in secondary forest land covers and slopes of 0-8%. Land cover and slope gradient affect the C-organic content. The highest C-organic content was obtained in secondary forest land cover with a flat slope with an area of 249.92 ha. While the lowest C-organic content was obtained in shrub land cover with a gentle slope with an area of 59.75 ha. The distribution of soil organic carbon content in Simbang District is dominated by the moderate category.